Aspectos socioeconômicos e ambientais dos empreendimentos de lavajatos do município de Pau dos Ferros-RN - Nunes, Felipe Magnus de Oliveira (Universidade Federal Rural do Semi-Árido, 2016)
This research aims to carry out a socio-economic and environmental diagnosis of the car wash of the municipality of Pau dos Ferros/RN, through the description of the activities, processes and services of these undertakings. As methodological procedures conducted a literature search and application of semi-structured questionnaire on 12 car wash. It was observed that the car wash of the municipality of Pau dos Ferros-RN present socioeconomic and environmental frailties in their activities, processes and services also confirmed that these establishments cause environmental impacts. It was found that the services provided by the car wash of Pau dos Ferros-RN correspond only washing of vehicles and oil changes, being performed by a diverse team. It was found that the main environmental impacts of these projects are related to the consumption of water, energy and raw materials; the generation of liquid effluents and solid residues. Evidence that the proposed environmental management to discuss the problems referred to following improvements on: Environmental Policy; Liquid Raw Materials; Solid Raw Materials; Production Process; Prevention processes; Treatment systems; Environmental quality of the process; Complementary aspects and; Environmental legislation, to fitness activities, processes and products of the washing of vehicles of the municipality of Pau dos Ferros/RN. Finally, studies are recommended on the quality of industrial liquid effluents and their possible effects on the environmental compartments of the study area.
Keywords: Lavajato; Limpeza de automóveis; Gerenciamento de efluentes líquidos; Car wash; Car cleaning; Liquid effluents management; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA